Si-Wei-Qing-Gan-Tang Improves Non-Alcoholic Steatohepatitis by Modulating the Nuclear Factor-κB Signal Pathway and Autophagy in Methionine and Choline Deficient Diet-Fed Rats - Xiao, Lingyun; Liang, Shu; Ge, Lanlan; Qiu, Shuling; Wan, Haoqiang; Wu, Shipin; Fei, Jia; Peng, Shusong; Zeng, Xiaobin (Frontiers in Pharmacology, 2020)
Si-Wei-Qing-Gan-Tang (SWQGT) is a Chinese medicine formula that is widely used as a folk remedy of herbal tea for the treatment of chronic hepatitis, like non-alcoholic steatohepatitis (NASH), around Ganzhou City (Jiangxi province, China). However, the underlying mechanisms of this formula against NASH are still unknown. This study aimed to explore the effect and mechanisms of SWQGT against NASH. A network pharmacology approach was used to predict the potential mechanisms of SWQGT against NASH. Then a rat model of NASH established by feeding the methionine and choline deficient (MCD) diet was used to verify the effect and mechanisms of SWQGT on NASH in vivo. SWQGT (1 g/kg/d and 3 g/kg/d) were given by intragastric administration. Body weight, liver weight, serum biochemical indicators, liver triglyceride and total cholesterol were all measured. Tumor necrosis factor-α (TNF-α), Interleukin (IL)-1β, IL-6 levels in the livers were evaluated using ELISA. Hematoxylin and eosin (HE) and Oil Red O staining were used to determine histology, while western blot was used to assess the relative expression levels of the nuclear factor-κB (NF-κB) pathway- and autophagy-related proteins. Functional and pathway enrichment analyses revealed that SWQGT obviously influenced inflammation-related signal pathways in NASH. Furthermore, in vivo experiment showed that SWQGT caused a reduction in liver weight and liver index of MCD diet-fed rats. The formula also helped to reduce hepatomegaly and improve pathological liver changes and hepatic steatosis. SWQGT likewise reduced liver TNF-α, IL-1β, and IL-6 levels and down-regulated p-NF-κB p65, p-p38 MAPK, p-MEK1/2, p-ERK1/2, p-mTOR, and p62, while up-regulating p-ULK1 and LC3II protein expression levels. SWQGT could improve NASH in MCD diet-fed rats, and this effect may be associated with its down-regulation of NF-κB and activation of autophagy.